Western blotting as a tool for the serodiagnosis of farmer's lung disease: validation withLichtheimia corymbiferaprotein extracts. Issue 4 (April 2015) - Rognon, Bénédicte; Reboux, Gabriel; Roussel, Sandrine; Barrera, Coralie; Dalphin, Jean‐Charles; Fellrath, Jean‐Marc; Monod, Michel; Millon, Laurence
Abstract : N/A: Electrosyneresis and double diffusion are immunoprecipitation techniques commonly used in the serological diagnosis of Farmer's lung disease (FLD). These techniques are reliable but lack standardization. The aim of this study was to evaluate Western blotting for the serodiagnosis of FLD. We carried out Western blotting with an antigenic extract of Lichtheimia corymbifera, an important aetiological agent of the disease. The membranes were probed with sera from 21 patients with FLD and 21 healthy exposed controls to examine the IgG antibody responses against purified somatic antigens. Given the low prevalence of the disease, 21 patients could be considered as a relevant series. Four bands were significantly more frequently represented in membranes probed with FLD sera (bands at 27.7, 40.5, 44.0 and 50.5 kDa) than those probed with control sera. We assessed the diagnostic value of different criteria alone or in combination. The diagnostic accuracy of the test was highest with the inclusion of at least two of the following criteria: at least five bands on the strip and the presence of one band at 40.5 or 44.0 kDa. Sensitivity, specificity and positive and negative predictive values were all 81 %, and the odds ratio was 18.06. Inclusion of bands of high intensity diminished rather than improved the diagnostic value of the test. We concluded that Western blotting is a valuable technique for the serodiagnosis of FLD. The industrial production of ready‐to‐use membranes would enable the routine use of this technique in laboratories, and provide reliable and standardized diagnostic results within a few hours.